The use and applications of the Soilscapes datasets - Farewell, Timothy S.; Truckell, Ian G.; Keay, Caroline A.; Hallett, Stephen H. (Cranfield University, 2011)
A Technical Manual to guide users through the uses and applications of the soilscapes datasets.

Soilscapes is one of the most popular datasets available from NSRI. It strips away confusing terminology and enables informed decision making by non-soil scientists who require an understanding of soil and how it affects the landscape. With Soilscapes, decision makers will gain a working knowledge of many fundamental soil-landscape processes for any region across England and Wales.